An assessment for attitudes consistent with sexual offending for use with offenders with intellectual disabilities - Lindsay, William R. (Legal and criminological psychology, 2007)
Background. Over the past 10 years, the focus of assessment and treatment for sex offenders has changed from the assessment of skills and deviant sexual preferences to the assessment and treatment of cognitions that might be considered to encourage or justify inappropriate sexual behaviour. There have been a few assessment measures of deviant sexual cognitions developed for adults in mainstream sex offender populations but none in less able populations. The present study describes an assessment questionnaire consisting of 7 scales for cognitions associated with rape, voyeurism, exhibitionism, dating abuse, stalking, homosexual assault and offences against children, designed to be used by sex offenders with intellectual disabilities. Method. Four groups of subjects were employed in this study - sex offenders, non-sexual offenders, non-offenders all with mild intellectual disabilities or borderline intelligence and a further group of normal men. All subjects completed the questionnaire and 86 subjects provided reliability data. Results. Each item was subjected to 3 tests of reliability. Retained items were required to achieve an item-to-total correlation of at least 0.4. Of the 7 scales, 5 achieved an internal consistency coefficient of 0.8 or greater. All scales successfully discriminated between groups even when the normal controls were eliminated because their scores were so low. Conclusions. It is possible to develop scales to assess cognitions related to types of offences which discriminate between sex offenders and other groups with intellectual disabilities. The final scales have robust statistical properties and can be used for clinical and research purposes. Some caution was noted in the use of attitudinal assessments for sex offenders.